Study of erbium disilicide and its application in Schottky source/drain silicon nanowire MOSFETs - Tan, Eu Jin (2010)
For ideal scaling, per generation (~3 years), a O.7x reduction in Metal Oxide Semiconductor Field Effect Transistor (MOSFET) dimensions is necessary to produce circuits with increased performance at reduced cost. 2 particular scaling factors to consider are : (1) source/drain (S/D) scaling which leads to increasing contact resistance (R_co), sheet resistance (R_sh) , and limitations in obtaining sharp lateral doping profiles, and (2) limitations in obtaining required effective drive current (I_d,sat) , and Subthreshold off-state leakage current (I_d,leak) with conventional planar transistor architecture. In this work, Erbium Disilicide (ErSi_2-x) was investigated as possible S/D material for Schottky S/D MOSFET (SSDMOS) architecture in an effort to address (1). In addition, various non planar transistor architectures using Gate-All-Around (GAA) Silicon Nanowire (SiNW) channel was fabricated in conjunction with SSDMOS architecture (SSDNWMOS) to address (2). ErSi_2-x advantageous for N-SSDMOS due to its low barrier to the inverted n-channel and epitaxy on Si substrates. However, to successfully implement ErSi_2-x for N-SSDMOS applications, problems related to intrinsic physical properties of ErSi_2-x thin films (e.g. ease of oxidation, and pyramidal structural defects etc.) have to be solved. The solid phase reaction mechanism in Er/Si system for disilicide formation as well as the characterization of the structural and electrical properties of different phases formed was carried out. The physical nature of pyramidal structural defects found on the silicide thin film was found to be due to several factors including biaxial compressive stress exerted by the Si substrate and fast diffusion of Si through the ErSi_2-x lattice. The ErSi_2-x/Si Schottky diodes show degraded Schottky barrier height (phi_Beff), and ideality factor (n) due to the structural defects which are likely sources of trap states. By applying Si substrate amorphization using a light Ar plasma sputter and Si preamorphization implant (PAI), the ErSi_2-x thin film was found to be are free of structural defects, leading to an overall improvement electrical performance which can be modeled using an inhomogenous Schottky contact model. In addition, in-situ capping layers of TiN and TiN/Ti were found to reduce structural defects density by ~5x which is believed to be due to a reduction in the biaxial compressive stress on the ErSi_2-x film during rapid thermal annealing.